Disjointed force polyhedra. (June 2018) - Lee, Juney; Mele, Tom Van; Block, Philippe
Abstract: This paper presents a new computational framework for 3D graphic statics based on the concept of disjointed force polyhedra. At the core of this framework are the Extended Gaussian Image and area-pursuit algorithms, which allow more precise control of the face areas of force polyhedra, and consequently of the magnitudes and distributions of the forces within the structure. The explicit control of the polyhedral face areas enables designers to implement more quantitative, force-driven constraints and it expands the range of 3D graphic statics applications beyond just shape explorations. The significance and potential of this new computational approach to 3D graphic statics is demonstrated through numerous examples, which illustrate how the disjointed force polyhedra enable force-driven design explorations of new structural typologies that were simply not realisable with previous implementations of 3D graphic statics. Highlights: A new computational framework for 3D graphic statics using disjointed force polyhedra. Iterative geometric algorithms for construction of force polyhedra with target face normals and areas. Flexible datastructure for a network of disjointed force polyhedra in equilibrium. Construction of disjointed polyhedral force diagrams for new structural typologies. Interactive force-driven design explorations with disjointed force polyhedra.